Addressing discourse differences in the writing of Russian engineering students and international researchers - Shpit, Elena I.; McCarthy, Philip M. (Language teaching research : LTR, 2025)
Virtually all researchers understand the requirement of presenting their studies in peer-reviewed English-medium journals. Russian scientific writers understand this necessity too; however, evidence suggests that these particular researchers are under-performing relative to similar non-native English speakers. The considerable challenge Russians face centers on articulating their ideas in English in the way that meets the norms and expectations of their international discourse community. That is, their writing is characterized as wordy, cumbersome, too academese, and syntactically complex. These issues need to be addressed in the early stages of developing writing skills. In this study, we address discourse differences between the scientific writing of Russian engineering students and that of international experts. Using the computational linguistics tools Coh-Metrix and Gramulator, we compare a corpus of students’ manuscripts with a similar corpus of experts’ published papers. We focused on six conceptual categories: readability, writing quality, cohesion, syntax, word choice, and genre purity. The overall results suggest that student writing differs significantly for multiple characteristics of text and discourse. A discriminant analysis provided a model that successfully predicts group membership and helps identify the most important issues in Russian student writing. Measures such as noun phrase density, genre purity, word age of acquisition, and variance in sentence length were found to be significant positive predictors of Russian student writing, whereas lexical diversity, adversative/contrastive connectives, adverbial phrase density, and word concreteness were significant positive predictors of expert writing. Our analysis allowed us to provide guidance for instructors, materials designers, as well as for technological assessment tools.